2019
DOI: 10.1089/chi.2018.0110
|View full text |Cite
|
Sign up to set email alerts
|

Cooking and Gardening Behaviors and Improvements in Dietary Intake in Hispanic/Latino Youth

Abstract: Background: School gardening interventions typically include cooking and gardening (CG) components; however, few studies have examined associations between CG psychosocial behaviors (attitudes, self-efficacy, and motivation), dietary intake, and obesity parameters. This study assessed the association between changes in CG behaviors with changes in dietary intake and obesity in participants of the LA Sprouts study, an after-school, 12-week, randomized controlled CG intervention conducted in four inner-city elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Knowledge and skills in relation to food and nutrition are a targetable outcome for nutrition education, as they can improve through education and skill development [ 52 ]. Prior research has shown that children involved in cooking activities have a higher vegetable intake compared to children who do not help [ 53 , 54 , 55 ]. Educating parents on successful ways to utilize their child’s help, coupled with equipping children with basic cooking skills, may be a potential strategy to overcome this barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge and skills in relation to food and nutrition are a targetable outcome for nutrition education, as they can improve through education and skill development [ 52 ]. Prior research has shown that children involved in cooking activities have a higher vegetable intake compared to children who do not help [ 53 , 54 , 55 ]. Educating parents on successful ways to utilize their child’s help, coupled with equipping children with basic cooking skills, may be a potential strategy to overcome this barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Increased fruit and vegetable consumption plays a significant protective role in the prevention of cancer and chronic diseases, such as cardiovascular disease and diabetes, and is also positively related to overall health status [4]. Self-efficacy as a key determinants of weekly dietary intake of fruits and vegetables among school going adolescents has also been reported by Landry BS et al, [5], Davis & Spaniol [6] and Laurie, Faber, & Maduna [7]. Consequently, any intervention targeting self-efficacy as a determinant of health promotion practice is paramount in improving weekly fruit and vegetable consumption [8].…”
Section: Introductionmentioning
confidence: 84%
“…Students' confidence towards weekly intake of fruits and vegetables can be enhanced by hands on activity through getting involved in gardening activities. Landry BS et al, [5] reported that school gardens increase the confidence of eating vegetables and ultimately increases the weekly dietary intake of fruits and vegetables. The choice of food and dietary habits are shaped early in life [5] and hence, hands on activities like cooking and gardening during school times will largely contribute to the confidence later in life to take fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two literature reviews on fruit and vegetable intake among children and youth who have participated in garden‐based interventions found that most studies suggest that gardens have a small but positive impact on children's fruit and vegetable consumption . Additional evaluations of young people who participated in garden programs have shown that students: are more willing to taste vegetables; consume more vegetables; demonstrate increased nutrition knowledge; show increased preference for vegetables; are more likely to eat fruits or vegetables as snacks or in a lunchroom setting; have increased dietary fiber intake; have a more positive attitude about fruits and vegetables in comparison to before they participated in the garden program; are better able to correctly identify fruits and vegetables; eat a larger variety of vegetables; have a sense of responsibility for the food system; and have an awareness of where food comes from . School garden interventions may also affect vegetable consumption at home.…”
mentioning
confidence: 99%